Heat flow of Uzbekistan: geology and interpretation - Zui, Vladimir I.; Andreyev, Dmitriy N.; Rakhmatullayev, Khikmatilla Kh. (Journal of the Belarusian State University. Geography and Geology, 2020)
The first determinations of the heat flow density in Uzbekistan, as well as in Central Asia as a whole, were carried out in the middle 1960s. In subsequent years, many researchers, primarily in connection with the search and exploration of oil and natural gas deposits, studied the geothermal field of the region. The data accumulated to date show a significant heterogeneity of the thermal field in both Uzbekistan and the adjacent territory of Central Asia. Rare wells were studied in the desert areas of Kyzyl Kum and Kara Kum. The heat flow in Uzbekistan varies over a wide range from 20–30 to approximately 100 mW/m2. Its high values are characteristic of intermountain depressions and blocks of the earth’s crust with a dense network of deep faults. The heat flow increases significantly in the southern and eastern parts of Uzbekistan, as well as in the neighbouring territories adjacent to the mountain structures of the Tien Shan and Pamir, characterized by high seismicity, tectonic and thermal activation. An updated map of the heat flow density of Uzbekistan was compiled and, separately for the Fergana Depression. They reflect a significant regional variability of the geothermal field. With the transition from the relatively flat territory of the Turanian Plate to mountain structures, the degree of differentiation by the heat flow increases significantly. This is typical of the entire orogenic Alpine-Himalayan Belt.
Keywords: geothermal investigations; geothermal field; heat flow; heat flow map; Uzbekistan